Medición de las propiedades eléctricas de la sangre humana utilizando un arreglo de microelectrodos coplanares - Prado Olivarez., J.; Gómez., R.; Díaz Carmona., J.; Padilla Medina., J.A.; Nadi., M. (Revista Mexicana de Ingenieria Biomedica, 2009)
This paper describes results in electrical properties measurement of human blood based on a platinum microelectrodes array, manufactured with electronic lithographic technique, and an impedance meter. The measurement frequency range was from 100 Hz up to 1 MHz and controlled blood temperature of 37 +- 0.5 C. According to with the experimental results in order to obtain the expected electrical properties valures, the polarization impedance effects must be taken into account. Such impedance effects were simulated in this work through an electrical model. The obtained data also show that for low measurement frequencies both the dielectric constant and the electric conductivity values of human blood are strongly influenced by the measurement cell geometry and parasite capacitances. The experimental results obtained by low and high measurement frequency values are compared with the results reported by other authors.